Protein Nanoparticles Made of Recombinant Viral Antigens: A Promising Biomaterial for Oral Delivery of Fish Prophylactics - Thwaite, Rosemary; Ji, Jie; Torrealba, Débora; Coll, Julio; Sabés, Manel; Villaverde, Antonio; Roher, Nerea (Frontiers in Immunology, 2018)
In the search for an eminently practical strategy to develop immunostimulants and vaccines for farmed fish, we have devised recombinant viral antigens presented as “nanopellets” (NPs). These are inclusion bodies of fish viral antigenic proteins produced in Escherichia coli. Soluble recombinant proteins are too labile to endure the in vivo environment and maintain full functionality, and therefore require encapsulation strategies. Yet when they are produced as nanostructures, they can withstand the wide range of gastrointestinal pH found in fish, high temperatures, and lyophilization. Moreover, these nanomaterials are biologically active, non-toxic to fish, cost-effective regarding production and suitable for oral administration. Here, we present three versions of NPs formed by antigenic proteins from relevant viruses affecting farmed fish: the viral nervous necrosis virus coat protein, infectious pancreatic necrosis virus viral protein 2, and a viral haemorrhagic septicemia virus G glycoprotein fragment. We demonstrate that the nanoparticles are taken up in vitro by zebrafish ZFL cells and in vivo by intubating zebrafish as a proof of concept for oral delivery. Encouragingly, analysis of gene expression suggests these NPs evoke an antiviral innate immune response in ZFL cells and in rainbow trout head kidney macrophages. They are therefore a promising platform for immunostimulants and may be candidates for vaccines should protection be demonstrated.